2011
DOI: 10.1186/1745-6150-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of recombination and selection in the genomes of Chlamydia trachomatis

Abstract: BackgroundChlamydia trachomatis is an obligate intracellular bacterial parasite, which causes several severe and debilitating diseases in humans. This study uses comparative genomic analyses of 12 complete published C. trachomatis genomes to assess the contribution of recombination and selection in this pathogen and to understand the major evolutionary forces acting on the genome of this bacterium.ResultsThe conserved core genes of C. trachomatis are a large proportion of the pan-genome: we identified 836 core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 91 publications
9
88
1
Order By: Relevance
“…Comparative genomic analyses of more than 65 clinical strains have provided evidence that LGT events within and between C. trachomatis biovars are natural and common occurrences (4,13,(126)(127)(128). Such analyses also indicated that genetic exchange is more likely between strains with tropism for the same site of infection (4,(126)(127)(128).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 95%
See 1 more Smart Citation
“…Comparative genomic analyses of more than 65 clinical strains have provided evidence that LGT events within and between C. trachomatis biovars are natural and common occurrences (4,13,(126)(127)(128). Such analyses also indicated that genetic exchange is more likely between strains with tropism for the same site of infection (4,(126)(127)(128).…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 95%
“…Such analyses also indicated that genetic exchange is more likely between strains with tropism for the same site of infection (4,(126)(127)(128). However, there are now multiple examples of interbiovar DNA exchange (4,122,127) in which strains with tropisms for different infection sites exchange DNA, suggesting that there are no absolute barriers to genetic exchange.…”
Section: Evidence Of Lgt Events Among Chlamydia Clinical Isolatesmentioning
confidence: 99%
“…In addition, almost all disease group-specific amino acids of Inc proteins encoded by genes likely under positive selection were found among proteins of LGV strains, and the majority of these amino acids localized in regions of the proteins predicted to face the host cell cytosol (Table 2). However, it must be clarified that other proteins in addition to Inc proteins are likely involved in the specificity of infection by LGV strains (8,30). Moreover, the overall determinants of tissue tropism of C. trachomatis should be complex and multifactorial and should certainly also include, e.g., the products of the trpRBA operon (10,19,51) or of the cytotoxin gene (11) and Tarp (34).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were essentially done as previously described (7,42). Briefly, for each strain, six tissue culture flasks with a surface area of 25 cm 2 containing monolayers of HeLa 229 cells were inoculated at a multiplicity of infection of 1; cells were harvested at 2,6,12,20,30, and 42 h postinfection by scraping in ice-cold phosphate-buffered saline. The cell suspension was sonicated to disrupt mammalian cells and promote bacterial release, followed by low-speed centrifugation at 4°C.…”
mentioning
confidence: 99%
“…Studying these genetically difficult organisms has become less arduous, with the recent advent of high-throughput sequencing technologies and workable genetic systems (Wang et al, 2011). While acquisition by chlamydiae of genetic material from other species is considered rare (Dugan et al, 2004), recombination within C. trachomatis, both in vitro and in vivo, appears to be relatively common (Dugan et al, 2004;Gomes et al, 2004Gomes et al, , 2007Harris et al, 2012;Jeffrey et al, 2010;Joseph et al, 2011;Somboonna et al, 2011;Srinivasan et al, 2012). Recombination has been documented between the lymphogranuloma venereum and urogenital biovars, fusogenic and non-fusogenic strains (Jeffrey et al, 2013), and strains with tropism for different tissues (Harris et al, 2012;Jeffrey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%